Too Good to be Abandoned - Yayah Atmajawati; Emmywati; Miya Dewi Suprihandari (Journal of Islamic Economics Perspectives, 2022)
Entrepreneurial activities require the spirit and creativity of the perpetrators in order to achieve success and become a leader. The ability to explore and manage the natural wealth that is around is often the capital for some people to start their activities to become entrepreneurs. The various natural resources that exist in many regions in Indonesia actually have great potential to be processed and developed by the community. This digging and managing activity will keep natural resources awake when they are processed using sufficient knowledge so as not to damage the environment that has been arranged. For this reason, the central government through the local government should pay attention to the "special needs" of the local community for the development of human resources in order to manage existing natural resources into something of high economic value and able to improve the economic capacity of the surrounding community, through training or empowerment activities or providing facilities and infrastructure for their activities.